Defense mechanisms and quality of life in military personnel with a burnout syndrome - Vojvodic, Aleksandra R; Dedic, Gordana; Djukic Dejanovic, Slavica (Vojnosanitetski pregled, 2021)
Abstract Background/Aim. Professional military personnel are exposed to a number of stressors during the war as well as in peacetime conditions that can cause some hidden or manifest disorders, especially anxiety and depression, but also the development of a burnout syndrome. The aim of our investigation was to determine the defense mechanisms and subjective assessment of quality of life and anxiety in professional military personnel of the Serbian Armed Forces with the burnout syndrome. Methods. The cross-sectional study included a total of 55 professional military personnel, from 25 to 55 years of age, without current mental problem. In the investigation, the Maslach Burnout Inventory (MBI), Defense Style Questionnaire (DSQ-40), World Health Organization Abbreviated Instrument for Quality of Life Assessment (WHOQOL-BREF) and Beck Anxiety Inventory were used. The statistical analysis included parametric and nonparametric descriptive statistics. Results. Emotional exhaustion and depersonalization were present in 10.9% of subjects and in 12.7% of subjects respectively, in moderate level, while personal accomplishment was present in 21.8% of subjects of high level. Humor was higher in the subjects with a moderate level of burnout on the personal accomplishment (PA) scale and altruism in the subjects with a low level of burnout on the depersonalization (DP) scale as well as acting-out and rationalization on the PA scale in the subjects with a moderate level of burnout. High level of anxiety was present in 14.5% of subjects. Conclusion. Professional military personnel with lower level of burnout were less anxious, use mature defense mechanisms and have a perception of better quality of life. When burnout is diagnosed, psychological interventions requires training through the adoption of mechanisms for overcoming everyday stress, which may affect the reduction of anxiety and the improvement of the quality of life. Professional assistance, including psychotherapy is required in severe cases.